2021
DOI: 10.3390/nu13051536
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Inflammatory Index, Dietary Patterns, Plant-Based Dietary Index and the Risk of Obesity

Abstract: Evidence on the association between various dietary constructs and obesity risk is limited. This study aims to investigate the longitudinal relationship between different diet indices and dietary patterns with the risk of obesity. Non-obese participants (n = 787) in the North West Adelaide Health Study were followed from 2010 to 2015. The dietary inflammatory index (DII®), plant-based dietary index (PDI) and factor-derived dietary pattern scores were computed based on food frequency questionnaire data. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 64 publications
4
49
1
2
Order By: Relevance
“…Furthermore, following a plant-based diet can be healthy and sustainable as it tends to create lower GHGE emissions [31,35], as well as being associated with a lower risk of obesity. A prospective study [36] that evaluated a Plant-Based Dietary Index (PDI) with obesity, suggested that the consumption of more plant-based foods and limiting animal-based diets might reduce the risk of obesity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, following a plant-based diet can be healthy and sustainable as it tends to create lower GHGE emissions [31,35], as well as being associated with a lower risk of obesity. A prospective study [36] that evaluated a Plant-Based Dietary Index (PDI) with obesity, suggested that the consumption of more plant-based foods and limiting animal-based diets might reduce the risk of obesity [36].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, even in the most Westernized pattern group (Q4), the daily intake of meat was only 73 g compared with that of the prudent group (46 g) [ 65 ], compared to 115 g in the U.S. ( Figure 9 ). The longitudinal relationships between different diet indices and dietary patterns with the risk of obesity were investigated in Australia, where dietary habits and the incidence of obesity are close to those in the U.S. [ 66 ]. The dietary inflammatory index (DII), plant-based dietary index (PDI), and factor-derived dietary pattern scores have been computed based on food frequency questionnaire data [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The longitudinal relationships between different diet indices and dietary patterns with the risk of obesity were investigated in Australia, where dietary habits and the incidence of obesity are close to those in the U.S. [ 66 ]. The dietary inflammatory index (DII), plant-based dietary index (PDI), and factor-derived dietary pattern scores have been computed based on food frequency questionnaire data [ 66 ]. In the adjusted model, the results of a multivariable log-binomial logistic regression showed that a prudent dietary pattern (RR Q5 vs. Q1 = 0.38; 95% CI: 0.15–0.96) and healthy PDI (RR = 0.31; 95% CI: 0.12–0.77) and overall PDI (RR = 0.56; 95% CI: 0.23–1.33) were inversely associated with obesity risk [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations